The Experience of Volunteers in Prisons in Portugal: A Qualitative Study - Salselas, Mónica; Pinto da Costa, Mariana (Frontiers in Psychiatry, 2022)
Background: Portugal is one of the countries that has a legal framework for volunteering, and there are different associations to support inmates through volunteering support. This volunteering can be beneficial for prisoners to address their social isolation and supporting them in the acquisition of skills and competencies to help them during their time in prison, but also beyond, supporting them in their resocialization and social reintegration in the community. However, little is known about the experiences of volunteers that provide such support to inmates. Methods: Semi-structured interviews were conducted to explore the experiences and motivations of volunteers who interact with prisoners in the prison context of the three main cities in Portugal (Coimbra, Lisbon, and Porto). The interviews were audio-recorded, transcribed, and analysed using the thematic analysis method. Results: Thirty-nine prison volunteers agreed to participate in this study (n=24 women, n=15 men), with two to thirty years of experience of volunteering. The main themes emerging from the analysis were ‘Different motivations to volunteer’, ‘Volunteers’ interactions with inmates', 'Volunteers' interactions with prison staff’, ‘Volunteering in prisons has an impact on volunteers’, ‘Volunteers’ perception of helping inmates’ and ‘More support to volunteering in prisons’. Conclusions: Community volunteers who support prisoners can develop positive and trusting relationships with the inmates, despite its challenges. These findings can raise awareness to volunteering in prisons as a potentially helpful intervention, and call for further research to better explore its long-term impact.